Mineral Tanah sebagai Indikator Stabilitas Tanah pada Daerah Berlereng: Studi Kasus Tombolopao Kabupaten Gowa - Asmita Ahmad; Christianto Lopulisa; A.M Imran,; Sumbangan Baja (Universitas Hasanuddin, 2018)
Soil forming process can influence soil stability, especially on a sloping area, which is currently related to landslides. This research aims to study mineral content in the soil as an indicator to evaluate soil stability in slope area. Soil texture analyzed with hydrometer and soil mineral analyzed with Kerr method. Soil parent rock comes from Tpbv (Tertiary Pliocene Baturape Volcanic) Formation that consists of lava, breccia, tuff, and conglomerate. Soil texture in A horizon dominated with silty clay loam and in B horizon with silty clay. Clay content in A horizon to B horizon increase ranges from 2-6%. Soils mineral have been weathering on the physical and chemical, which caused cracking on minerals lattice and formed clay minerals inside it. The presence of clay minerals between soil mineral particles can cause mutual repulsion force and cause friction particles that triggering the movement of particles in a small scale when soil saturated by water and triggers soil movement (landslide).